Działalność siedleckiego komitetu wojskowo-rewolucyjnego w sierpniu 1920 roku - Borek, Paweł (Komunizm: System - Ludzie - Dokumentacja, 2014)
The article shows the almost weekly Siedlce occupation by the Red Army in August 1920 and the course of the organization and functioning of the revolutionary committee in this city. After the evacuation of Polish troops from the Bug river on the southern Podlasie entered the Red Army, whose task was: establishment of communist structures in each of the affected villages, farm and factory. County, city, municipal, homestead, and factory revolutionary committees designated by the Red Army had the character of civil-military, and directly subordinate to the Revolutionary Military Council was the army, operating in the area. Most members of the revolutionary committees on occupied territories were Jews, especially activists of Bund and Poalej Zion, with whom entering to ethnically Polish lands Soviets could easily communicate in Russian language. Short-term occupation of the Siedlce by the Red Army ended with the start of the Polish counteroffensive from Wieprz river in 16th August, 1920. The activities of Soviet power in this city did not result in major changes in the political and economical cases, and the attempt to raise the Polish population to the idea of communism was completely failed.